The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/aem.70.3.1328-1335.2004
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Destroying Soft Rot Fungi in the Historic Expedition Huts of Antarctica

Abstract: Three expedition huts in the Ross Sea region of Antarctica, built between 1901 and 1911 by Robert F. Scott and Ernest Shackleton, sheltered and stored the supplies for up to 48 men for 3 years during their explorations and scientific investigation in the South Pole region. The huts, built with wood taken to Antarctica by the early explorers, have deteriorated over the past decades. Although Antarctica has one of the coldest and driest environments on earth, microbes have colonized the wood and limited decay ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 18 publications
(22 reference statements)
1
79
0
2
Order By: Relevance
“…In general, the fungal communities of Antarctic soils are dominated by filamentous ascomycetes and basidiomycete yeasts (Connell et al 2008; Arenz and Blanchette 2011). Filamentous basidiomycetes that are typically known as wood-decay fungi in temperate ecosystems have been very rarely isolated in Antarctica (Blanchette et al 2004; Ludley and Robinson 2008). Fungi in Zygomycetes are also isolated with some frequency in Antarctic (Lawley et al 2004).…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the fungal communities of Antarctic soils are dominated by filamentous ascomycetes and basidiomycete yeasts (Connell et al 2008; Arenz and Blanchette 2011). Filamentous basidiomycetes that are typically known as wood-decay fungi in temperate ecosystems have been very rarely isolated in Antarctica (Blanchette et al 2004; Ludley and Robinson 2008). Fungi in Zygomycetes are also isolated with some frequency in Antarctic (Lawley et al 2004).…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…A group of cold-adapted fungi decompose woody structures and artefacts left by the early polar explorers in Antarctic. Blanchette et al (2004) first reported an unusual form of soft rot decay caused by Cadophora species which can cause degradation of the historic huts and artefacts. This type of decay has subsequently been found to be prevalent in historic woods and in soils from the immediate vicinity of the huts at many Antarctic locations and variety of filamentous fungi and yeasts such as Cadophora, Cladosporium, Cryptococcus and Geomyces species were discovered with a high frequency (Arenz et al 2006; Arenz and Blanchette 2009; Blanchette et al 2010).…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only soft rot fungi has been observed in the decomposition of wooden structures, mostly old huts, in Antarctica (Blanchette et al 2004) and it was concluded that the harsh climate conditions preclude the development of white and brown rot fungi. This would exclude all wood decomposing Basidiomycota from the biota of Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have taken place both in relatively easily accessible and more benign locations (Azmi et Seppelt 1990, Cheryl et Seppelt 1999 and in more environmentally challenging areas such as the Victoria Land Dry Valleys (Friedmann et al 1985, Cameron et al 1971. The occurrence of fungi associated with humanassociated habitats and artifacts, such as in historical huts, have been studied extensively by Tubaki (1961), Martin (1988), Blanchette (2000), Blanchette et al (2004) and Held et al (2005).…”
Section: Antarctic Microfungal Diversitymentioning
confidence: 99%